2013
DOI: 10.1149/05701.1395ecst
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ceria Addition in SOFC Anodes on Sulfur Poisoning

Abstract: In SOFCs, a wide range of fuel gases can be applied, but fuel impurity tolerance may be desired. By applying gadolinia-doped ceria (GDC) anode material, we analyzed power generation characteristics and internal reforming followed by high-resolution electron microscopy in order to moderate sulfur poisoning. Effect of ceria addition into the anodes layers on sulfur poisoning is systematically analyzed and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…On the other hand, many previous investigations have concluded that the formation of bulk cerium sulfides is unlikely to occur at the temperatures and concentrations used in this work [3,19,60]. While some studies have reported improved tolerance with ceria, it is not usually considered to be any better performing than a nickel as an anode when exposed to H 2 S-rich gas [3,19,51].…”
Section: Discussion On H 2 S Poisoning Mechanismmentioning
confidence: 75%
“…On the other hand, many previous investigations have concluded that the formation of bulk cerium sulfides is unlikely to occur at the temperatures and concentrations used in this work [3,19,60]. While some studies have reported improved tolerance with ceria, it is not usually considered to be any better performing than a nickel as an anode when exposed to H 2 S-rich gas [3,19,51].…”
Section: Discussion On H 2 S Poisoning Mechanismmentioning
confidence: 75%